Students’ Attitudes toward the Use of Podcast as Digital Material in EFL Classroom - Yasmiatun Yasmiatun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Some previous studies mentioned that students showed a negative attitude toward EFL learning because they felt bored with printed materials like textbooks. Hence, this study was conducted to implement digital material in EFL classrooms and observe students' attitudes and difficulties in experiencing digital material. Moreover, 30 students from eleven grades used podcasts as digital material to learn exposition paragraphs. This study used questionnaires and interviews as the data collection to describe students' cognitive, affective, and behavioral attitudes as well as the difficulties in using the digital material. This study revealed that students showed a positive cognitive attitude in understanding and comprehending digital material. While the use of podcasts could assist them in producing the exposition text, it also triggers their critical thinking. Besides, students also felt interested and happy because they could choose their podcast as the learning material, and it reflected a positive affective attitude. The students' activeness in classroom interaction was improved after using the digital material, and it showed their positive behavioral attitude.Furthermore, students also faced some difficulties, such as acquired the limitation of an internet connection to access the podcast and being confused about choosing a reliable podcast. In addition, this study showed that podcasts reflect the function of supplementary and complementary digital learning material in EFL classrooms. Finally, this study followed by suggestions for the English teacher to improve the teaching and learning process using digital material. Keywords: Attitudes, Digital Material, Exposition text, Podcast